Manajemen Risiko Investasi Bank Syariah - Novi Tri Oktavia (Jurnal Ilmiah Mahasiswa Perbankan Syariah (JIMPA), 2023)
This research is motivated by the uncertainty of the time and amount of return that will be received by investors. So that Islamic Banking as one of the managers of Hajj funds must minimise risk by making appropriate investment risk management. This research uses a qualitative approach with the type of library research. This research tries to provide answers to the problem of sukuk investment using Hajj funds and related to the use of Hajj funds for sukuk investment in Islamic views explained through data and information sourced from books, journals, articles, news and relevant reports. The results of this study indicate that the risks carried out by Islamic Banks in managing Hajj funds to be invested in sukuk are liquidity risk, default risk, and sharia non-compliance risk. The efforts of Islamic Banks as a form of liquidity risk management in their investments, including in Hajj funds, are to calculate the projected budget for the Hajj fund. Meanwhile, in managing the risk of default, Islamic banks allocate funds for the purpose of investment loss reserves. In addition, Islamic banks use ijarah al-khadamat contracts that have received a statement of sharia conformity from DSN-MUI Number B-118/DSN-MUI/III/2009 dated 31 March 2009.